Exploring Parents' Perceptions Toward Early Childhood English Language Education in Jakarta - Vicontie, Cecilia; Santosa, Imam (STAIRS: English Language Education Journal, 2023)
This study investigates parents' perceptions of early childhood English language education in Jakarta, Indonesia. With an increasing emphasis on English proficiency in a globalized world, understanding parental attitudes toward introducing English early age is essential. This research employed a mixed-methods approach, utilizing a survey questionnaire to gather insights from 52 parents, consisting of 40 mothers and 12 fathers, whose children were between 3 to 6 years old. The survey revealed that 92% of parents agreed that early English education enhances language development, 88% believed it provides a competitive edge, 83% considered it crucial for opportunities, and 74% saw its potential to boost cognitive skills. In-depth interviews were conducted with 16 participants, selected through purposive sampling, to delve deeper into parental perceptions, providing further insight. The findings underscore parents' collective recognition of the positive impact of early English education on language development and cognitive skills, presenting a valuable resource for parents seeking informed decisions about their children's early language learning journey. The study offers input for educators, policymakers, and curriculum designers aiming to create effective early English programs resonating with parental perspectives.